Evaluasi Angka Kebutuhan Nyata Operasi Dan Pemeliharaan Pada Bangunan Pantai Talud Seli Kota Tidore Kepulauan - Ahmad, Badrun; K. Misbah, Zulkarnain; Taufiq Y.S, Muhammad (Journal of Science and Engineering, 2024)
AbstractThis research uses a probability distribution method and a probability test to calculate the planned rainfall. Buoy method for calculating river discharge. Rational method, Kirpich method, Mononobe method for calculating flood discharge and Manning method for calculating planned and existing cross-sectional capacity. Flood discharge on the Aru River for a return period of 2 years, 23.18 m³/second for a return period of 5 years, 28.26m³/second for a return period of Seli Beach which is located in the City of Tidore Islands. This research is to determine the level of damage to the embankment building and the appropriate maintenance method for the coastal protection structure. The method used in the research is a direct survey method in the field. The results of this research showed that the length of the building was 462 meters, the results of the calculation of the condition index for coastal safety buildings in Seli Village, Tidore Islands City were at a level of damage of 2.5 - 3.5, which shows that this riparian dam was in light - heavy damage. This 462 meter long dam requires regular and periodic repairs and maintenance. Based on the results of the AKNOP preparation carried out, the total operational costs required for the talud building are obtained at Rp. 59,334,547.62, and the cost of maintaining the talud is Rp. 780,680,536.07.g 10 years, 31.45 m³/second for a return period of 20 years, 34.51 m3/second. The existing average discharge of the Aru River is 24.14 m³/second, for the planned discharge of the Aru River cross-section it is 78.808 m³/second and for the embankment design model which is in accordance with flood discharge the embankment maintenance height is 1 m for embankment height of 2.5 m .Keywords— Talud, Seli, Aknop, Evaluation AbstrakPenelitian ini menggunakan metode distribusi probabilitas dan uji probabilitas. Metode pelampung untuk menghitung debit sungai. Metode rasional, metode Kirpich, metode Mononobe untuk menghitung debit banjir. Debit banjir pada Sungai Aru untuk periode ulang 2 tahun, 23,18 m³/detik untuk periode ulang 5 tahun, 28,26m³/detik untuk periode ulan Pantai Seli yang terletak di Kota Tidore Kepulauan. Tujuan dari penelitian ini adalah untuk mengetahui tingkat kerusakan pada bangunan talud dan metode pemeliharaan yang tepat terhadap bangunan pengaman pantai tersebut. Metode yang di gunakan pada penelitian adalah metode survei langsung di lapangan. Hasil penelitian ini diperoleh panjang bangunan 462 meter, hasil perhitungan indeks kondisi bangunan pengaman pantai di Kelurahan Seli Kota Tidore Kepulauan berada pada tingkat kerusakan 2,5 – 3,5 yang menunjukan talud ini dalam kerusakan ringan – berat. Panjang talud 462 meter ini memerlukan perbaikan dan pemeliharaan secara rutin dan berkala. Berdasarkan hasil penyusunan AKNOP yang dilakukan, sehingga diperoleh total biaya operasional yang dibutuhkan untuk bangunan talud Rp. 59.334.547,62, dan biaya pemeliharaan talud sebesar Rp. 780.680.536,07.g 10 tahun, 31,45 m³/detik untuk periode ulang 20 tahun, 34,51 m3/detik. Debit rata-rata eksisting Sungai Aru sebesar 24,14 m³/detik, untuk debit rencana penampang sungai Aru sebesar 78,808 m³/detik dan untuk model desain tanggul yang sesuai dengan debit banjir di dapat tinggi jagaan tanggul 1 m untuk tinggi tanggul 2,5 m.Kata kunci— Talud, Seli, Aknop, Evaluasi